2019
DOI: 10.1111/jdv.15875
|View full text |Cite
|
Sign up to set email alerts
|

The epidemic of methylisothiazolinone contact allergy in Europe: follow‐up on changing exposures

Abstract: Background Methylisothiazolinone (MI) has caused an unprecedented epidemic of contact allergy in Europe and elsewhere. Subsequently, regulatory action has been taken, at least in Europe, aiming at reducing risk of MI sensitization. Objective To follow‐up on the prevalence of contact allergy to MI in consecutively patch tested patients and assess the spectrum of products containing MI or methylchloroisothiazolinone (MCI)/MI in patients positive to MI which elicited current allergic contact dermatitis. Methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
45
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 21 publications
7
45
2
3
Order By: Relevance
“…Nevertheless, MI and other isothiazolinones are still important contact allergens, and exposure and sensitization trends warrant close surveillance. 22 While 2-bromo-2-nitro-1,3-propanediol was phased out of the baseline series in 2013-2014, IPBC had been added, yielding positive reactions in about 1% of the patients tested. Concerning patch testing with formaldehyde in the IVDK, it should be noted that formaldehyde is still tested at 1% aqua and not 2% aqua as recommended in the European baseline series.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, MI and other isothiazolinones are still important contact allergens, and exposure and sensitization trends warrant close surveillance. 22 While 2-bromo-2-nitro-1,3-propanediol was phased out of the baseline series in 2013-2014, IPBC had been added, yielding positive reactions in about 1% of the patients tested. Concerning patch testing with formaldehyde in the IVDK, it should be noted that formaldehyde is still tested at 1% aqua and not 2% aqua as recommended in the European baseline series.…”
Section: Discussionmentioning
confidence: 99%
“…21 Consequently, the use of MCI/MI and MI in leave-on cosmetics was prohibited in Europe in 2016 and 2017, respectively, 22,23 and in 2018 the concentration of MI in rinse-off cosmetics was reduced by the European Commission to the same level as MCI/MI, ie, 15 ppm. 24 The introduction of similar legislative measures around the world led to an observable decrease in the incidence of non-occupational ACD due to isothiazolinones, mainly from cosmetic products, 12,16,25,26 while an increase in occupational ACD was observed in some countries after the epidemic due to the lack of legal restrictions of the use of isothiazolinones in industrial products. 26 There are only limited data on ACD from MCI/MI and MI in Turkey, 27,28 where MCI/MI and MI up to 15 ppm and 100 ppm, respectively, are currently allowed only in rinse-off cosmetics.…”
mentioning
confidence: 99%
“…The incidence of ACD to methylisothiazolinone (MI) has been unprecedentedly high in Europe and other parts of the world. Regulation (and prior pre-emptive partial withdrawals from the market) have led, in the EU and those countries adopting its regulation, to a significant decline, for instance, from 5.97% in 2015 to 4.72% in 2016, and further to 2.96% in 2017, according to an EECDRG study [99]. The same study also identified a significant shift of currently clinically relevant products, that is, those products which elicited ACD leading to consultation for patch testing, from leave-on cosmetics to rinse-off cosmetics and household products.…”
Section: Preservativesmentioning
confidence: 99%